2007
DOI: 10.1007/s00535-007-2085-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in preS genes of genotype C hepatitis B virus in patients with chronic hepatitis B and hepatocellular carcinoma

Abstract: PreS deletion mutations of genotype C HBV might play a role in HBV-related hepatocarcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
2
41
2
1
Order By: Relevance
“…HBeAg expression and high viral load are associated with an increased risk of HCC (18,19). Some mutations in the PreS and the EnhII/BCP/Precore regions have been associated with the development of HCC (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our recent meta-analysis using published data up to August 31, 2008 has shown that HBV PreS mutations, C1653T, T1753V, and A1762T/G1764A, are associated with an increased risk of HCC (30).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…HBeAg expression and high viral load are associated with an increased risk of HCC (18,19). Some mutations in the PreS and the EnhII/BCP/Precore regions have been associated with the development of HCC (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our recent meta-analysis using published data up to August 31, 2008 has shown that HBV PreS mutations, C1653T, T1753V, and A1762T/G1764A, are associated with an increased risk of HCC (30).…”
Section: Introductionmentioning
confidence: 98%
“…In Mainland China, an endemic area with almost one third of the HBsAg carriers found worldwide (1), HBV genotypes and mutations have been investigated in a limited number of the hospital-based patients and selected geographic areas (21,22,24,25,27,31,32). However, no community-based epidemiologic study with sufficient participants has shown nationwide distribution of HBV genotypes and the prevalence of the HCC-associated viral mutations as well.…”
Section: Introductionmentioning
confidence: 99%
“…The HBV ENV ORF encodes three envelope proteins of graduating length: large (pre-S1, pre-S2, and S), middle (pre-S2 and S), and small/surface (S). The mRNAs of these envelope proteins are transcribed from a single ORF; however, each has its own initiation codon (11). In general, the number of pre-S mutations can increase during the progression of CHB (12), and pre-S mutations are more prevalent in patients with HCC and liver cirrhosis (13).…”
mentioning
confidence: 99%
“…The latest approach by using Mboll PCR restriction analysis also identified a novel mutation in pre-S2, it is reported that F141L mutation was significantly related to HCC, even in comparison to live cirrhosis among 241 Korean patients (Mun et al, 2011). As for pre-S deletion, it was (Gao et al, 2007) reported that these mutations were more commonly found in the patients with HCC that in the chronic hepatitis B or asymptomatic carrier, suggesting pre-S deletion might involved in HBV-related hepatocarinogenesis. Mutations in basal core promoter may also involved in the development of carcinoma, the result of direct sequencing revealed that mutations including A1896, A1899 and multiple mutations T1762/A1764+A1896, T1762/A1764+A1899, and T1762/A1764+A1896+A1899 were more common in cirrhotic hepatocellular carcinoma group and non-cirrhotic hepatocellular carcinoma than chronic hepatitis B patients (Zheng et al, 2011).…”
Section: Hbv Infectionmentioning
confidence: 98%